Diskresi dalam Penanggulangan Bencana di DIY dengan Paradigma Kontinjensi - Ishviati Joenaini Koenti (Jurnal Hukum IUS QUIA IUSTUM, 2016)
The main problem in this study is to examine the developments of the contingency plans that have not or have been made and whether it is activated or not. If it is activated, how is the evaluation of its implementation and if not activated, how is its monitoring and how is the supervision of its budget? The method used in this research is normative-juridical. The study concluded that not all contingency plans have been made in the types of disaster. Some contingency plans have been made. in Yogyakarta there are 4, 3 are in Sleman Regency, 3 in Kulonprogo and in Gunung Kidul. Overall, there are 8 contingency plans already implemented. For the places that have not been activated, the state is returned to the original condition. To follow-up and evaluation of post-contingency plan, the activation or inactivity should be uniform. It is necessary to put in the draft of Raperda on the changes in the draft of Regional Regulation About Disaster Management.